Gap between awareness and practices of cosmeceuticals among young adults of Panjab University - Mitali; Walia, Dinesh Kumar; Sharma, Manoj Kumar; Prashar, Savita (International Journal Of Community Medicine And Public Health, 2023)
Background: Cosmeceuticals are cosmetic products that contain bioactive ingredients with pharmaceutical properties. These products are designed to improve skin health and appearance by providing functional benefits beyond traditional cosmetics. However, there exists a noticeable gap between the awareness of these specialized formulations and their practical application by consumers. Methods: This was a descriptive cross-sectional study conducted among 171 students. The data was collected by conducting personal interviews using an interview /survey schedule designed specifically for this study. Descriptive and analytical statistics were utilized to get the necessary results. Results: The study included 171 participants, with (24.6%) males and (75.4%) females. Notably, a high level of awareness (100%) and utilization (60.8%) was observed for essential skincare products where females tend to use cosmeceuticals more frequently. Also, the cleansers (100%), moisturizers (100%), and sunscreen (100%) were most valued and were daily incorporated into skincare routines. Conclusions: The findings revealed the prevalence of cosmeceutical awareness and usage, with cleansers, moisturizers, and sunscreen being the most recognized and adopted products. However, a notable gender discrepancy in the usage of certain products suggests variations in preferences and concerns among males and females. Overall, this research contributes to the understanding of cosmeceutical usage patterns, and knowledge gaps. Future efforts should focus on exploring these gaps and promoting responsible and well-informed consumer practices, ultimately fostering a healthier approach to skincare and cosmeceutical products.